Mind mapping assisted with picture media using learning ownership approach integrated with PjBL to increase students’ collaboration skills and cognitive learning outcomes - Zizah Estuning Erina; Herawati Susilo; Denny Setiawan (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Collaboration skills are closely related to cognitive learning outcomes. Learning made by collaborating can improve students' understanding of the material, so that student learning outcomes are maximized. Cognitive learning outcomes of students in class X-I SMA Negeri 1 Turen on Virus material show low results with an average score of 56 and collaboration skills of 64% which are included in the proficient criteria. This study aims to improve collaboration skills and cognitive learning outcomes through the application of mind mapping assisted by image media using the Learning Ownership approach integrated with Project Based Learning (PjBL). This type of research is a Lesson Study-based Classroom Action Research conducted in two cycles. The results showed that the implementation of mind mapping assisted by image media using the Learning Ownership approach integrated with PjBL can improve collaboration skills and cognitive learning outcomes of students in class X-I SMA Negeri 1 Turen. The percentage of students' collaboration skills increased from 73% in cycle I to 82% in cycle II. Cognitive learning outcomes also improved as indicated by the classical completeness of students in cycle I of 41.6% (incomplete) increased to 100% (complete) in cycle II and the N-Gain value of cycle I of 0.53 which is included in the moderate criteria, in cycle II it increased to 0.73 which is included in the high criteria.